Respostas
respondido por:
3
Vamos calcular
f(5) => f(5) = 5 - 3 * 5 = 5 - 15 = -10
f(1) => f(1) = 5 - 3 * 1 = 5 - 3 = 2
g(3) => g(3) = 7 * 3 - 8 = 21 - 8 = 14
g(8) => g(8) = 7 * 8 - 8 = 56 - 8 = 48
f(5) + g(3) = -10 + 14 = 4
f(1) + g(8) = 2 + 48 = 50
Assim temos: 4 / 50 = 2 / 25
Bons estudos.
marcoslimabm:
De um melhor resposta ae. vlw
respondido por:
5
f(5) + g(3)
f(1) . g (8)
f(5) = 5 - 3.5 = 5 -15 = -10
g(3) = 7.3 - 8= 21-8 = 13
f (1) = 5 - 3.1 = 5-3 = 2
g(8) = 7.8 - 8 = 56-8 = 48
-10 +13 = 3 = 1
2 .48 96 32
f(1) . g (8)
f(5) = 5 - 3.5 = 5 -15 = -10
g(3) = 7.3 - 8= 21-8 = 13
f (1) = 5 - 3.1 = 5-3 = 2
g(8) = 7.8 - 8 = 56-8 = 48
-10 +13 = 3 = 1
2 .48 96 32
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás